İlm-i Servet - Paşa, Münif (Politics, 2021)
The Science of Wealth was written by Münif Pasha, who features large in our history of science and philosophy. The work was used as a textbook by the Ottoman Law School, and took its place among the texts that carried modern economic knowledge to the Ottoman world of thought. The period that started in the second half of the 19th century and continued up until the foundation of the Republic was a time of remarkable contributions to economic literature. The fact that The Science of Wealth remains an important part of this body of literature and reflects the economic knowledge of period in its discussions served as the basis for In The Science of Wealth, Münif Pasha defends the idea of a liberal economy, although his criticisms of some of the views of Adam Smith and Malthus differentiate his work from other books in the economics field at the time. Issues, such as private property, the division of labour, freedom of industry and trade, fixed pricing, customs and interest, all of which are highly important in the creation of a liberal transformation to an economic, political, administrative, legal, religious and social structure, are among the headings in the Science of Wealth. The original, translated and simplified texts allow the work to reach a broader audience. It is hoped that the study will increase the level of interest in our economics and science history literature.